Exact Ordinary Differential Equation

2 views (last 30 days)
JC.UT on 9 Apr 2021
Edited: JC.UT on 9 Apr 2021
syms y(x)
ode=y*(1-x^2)*(diff(y))== ((x*y^2)-(cos(x)*sin(x)))
ode(x) =
-y(x)*(x^2 - 1)*diff(y(x), x) == x*y(x)^2 - cos(x)*sin(x)
sol =
((C1 - cos(x)^2)*(x - 1)*(x + 1))^(1/2)/(x^2 - 1)
-((C1 - cos(x)^2)*(x - 1)*(x + 1))^(1/2)/(x^2 - 1)
Did I properly tranlate the problem below correctly using the right syntax and operations ? Can you please check my code, is it correct ?

Accepted Answer

Samuel Brewton
Samuel Brewton on 9 Apr 2021
I just ran it through and got the same solution so it seems to check out.

More Answers (0)




Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by